Phytohormone Mediation of Interactions Between Plants and Non-Symbiotic Growth Promoting Bacteria Under Edaphic Stresses - Kudoyarova, Guzel; Arkhipova, Tatiana; Korshunova, Tatiana; Bakaeva, Margarita; Loginov, Oleg; Dodd, Ian C. (Frontiers in Plant Science, 2019)
The capacity of rhizoshere bacteria to influence plant hormonal status, by bacterial production or metabolism of hormones, is considered an important mechanism by which they promote plant growth and productivity. Nevertheless, inoculating these bacteria into the plant rhizosphere may produce beneficial or detrimental results depending on bacterial effects on hormone composition and quantity in planta, and the environmental conditions under which the plants are growing. This review considers some effects of bacterial hormone production or metabolism on root growth and development and shoot physiological processes. We analyze how these changes in root and shoot growth and function help plants adapt to their growth conditions, especially as these change from optimal to stressful. Consistent effects are addressed, along with plant responses to specific environmental stresses: drought, salinity and soil contamination (with petroleum in particular).